Development Of Hots-Based Test Questions Wayground On Basic Food Processing Techniques In Culinary Vocational School - Elok Fajriah; Lucia Tri Pangesthi; Luthfiyah Nurlaela; Diwyacitta Antya Putri (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
The availability of assessment instruments that measure Higher Order Thinking Skills in basic food processing techniques is still limited. Therefore, an appropriate instrument is needed to evaluate students’ higher-order thinking abilities. This study aimed to develop and examine the quality of a HOTS-oriented test instrument on basic food processing techniques. The research employed a Research and Development (R&D) method using the 4D model (define, design, develop, and disseminate). The test was implemented through Wayground, an online interactive learning platform used to create and administer digital quizzes and assessments. The research subjects consisted of 59 students. Data analysis included item validity using Product Moment correlation, reliability using Cronbach’s Alpha, as well as analysis of item difficulty, discrimination index, distractor effectiveness, and completion time. The results indicated that 28 out of 55 items (50.9%) were valid. The reliability coefficient reached 0.81, categorized as very high. The difficulty level was dominated by moderate items (57%), followed by easy (39.5%) and difficult items (3.5%). The discrimination index showed fair (32%), good (43%), and very good (25%) categories. Distractor effectiveness was mostly in the good (57%) and very good (25%) categories. The fastest average completion time was 22 seconds, while the longest was 1 minute and 17 seconds. These results indicate that the instrument is feasible for measuring students’ higher-order thinking skills in basic food processing techniques.